Increase in pediatric recurrent fever evaluations during the first year of the COVID-19 pandemic in North America - Mansfield, Leanne M.; Lapidus, Sivia K.; Romero, Samira Nazzar; Moorthy, Lakshmi N.; Adler-Shohet, Felice C.; Hollander, Matthew; Cherian, Julie; Twilt, Marinka; Lionetti, Geraldina; Mohan, Smriti; DeLaMora, Patricia A.; Durrant, Karen L.; et al. (Frontiers in Pediatrics, 2023)
The impact of the COVID-19 pandemic on new diagnoses of recurrent fevers and autoinflammatory diseases is largely unknown. The Childhood Arthritis and Rheumatology Research Alliance (CARRA) PFAPA/AID Working Group aimed to investigate the impact of the COVID-19 pandemic on the number of pediatric patients evaluated for recurrent fevers and autoinflammatory diseases in North America. The absolute number of new outpatient visits and the proportion of these visits attributed to recurrent fever diagnoses during the pre-pandemic period (March 1, 2019, to February 29, 2020) and the first year of the COVID-19 pandemic (March 1, 2020, to February 28, 2021) were examined. Data were collected from 27 sites in the United States and Canada. Our results showed an increase in the absolute number of new visits for recurrent fever evaluations in 21 of 27 sites during the COVID-19 pandemic compared to the pre-pandemic period. The increase was observed across different geographic regions in North America. Additionally, the proportion of new visits to these centers for recurrent fever in relation to all new patient evaluations was significantly higher during the first year of the pandemic, increasing from 7.8% before the pandemic to 10.9% during the pandemic year (p<0.001). Our findings showed that the first year of the COVID-19 pandemic was associated with a higher number of evaluations by pediatric subspecialists for recurrent fevers. Further research is needed to understand the reasons behind these findings and to explore noninfectious triggers for recurrent fevers in children.